Study of Beef Availability Potential in Yogyakarta Special Province (DIY) through Multi Criteria Analysis (MCA) Model by Spatial Geographic Information System - Dwi Aulia Puspitaningrum; Masyhuri Masyhuri; Slamet Hartono; Jamhari Jamhari (agriTECH, 2018)
The increasing human population and income per capita in Indonesia have many impacts to the demand of food, not only staple food but also the secondary food too, including meat and beef demand. Based on data from Central Statistics Bureau of 1995–2016, beef demand in Indonesia has been increasing. This condition must be anticipated by preparing the supply, especially the availability of beef in Daerah Istimewa Yogyakarta province. In Yogyakarta city, one of the regencies of DIY, the demand rate grows by 3.2%/year, higher than the supply growth rate by 2.08 %/year.  This gap needs to be thought through the case of scarcity of beef on the market. This study aimed to identify the potential of supply in five parameters i.e.: beef population, the availability of semen for artificial insemination (IB), the availability of livestock feed plants (HMT), the number of cows that enter DIY, and the number of cows that exit from DIY. A model Spatial Geographic Information Systems (SGIS) has been used in this study. The study revealed the most potential area for the development of beef agribusiness, based on the availability side, was Gunung Kidul Regency, and the less potential was Yogyakarta municipality.